Ligand-free CuSO4-Catalyzed C-N Coupling Reaction of Aryl Halides with Alkylamines or N-heterocycles in Aqueous Solution System - Yang, Hua; Zhang, Xiuli; Si, Jingyu (Asian Journal of Chemistry, 2013)
C-N coupling can be achieved successfully under 80 ºC in aqueous nBu4NOH using CuSO4 as a catalyst. The study of substrate applicability demonstrated that the C-N coupling reaction of aryl iodides and bromides with alkylamines or N-heterocycles could be completed smoothly in this catalytic system.